IMPLEMENTASI AKAD SYIRKAH PADA BISNIS WARALABA AYAM GORENG PERSPEKTIF HUKUM EKONOMI ISLAM (STUDI PADA D’BESTO PT. SETYA KULINER MANDIRI, JAKARTA SELATAN) - Afifah, Fitri; Aminulloh, Ali; Maulana, Rizal (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
This research discusses the application of the syirkah contract in the d'BestO franchise business, a local brand operating in the fast food industry. The objective of this study is to analyze the implementation of the syirkah contract within the franchise business model and assess its compliance with Islamic economic law principles. The research adopts a qualitative approach, utilizing field research. The data collection methods employed include interviews and direct observations with parties involved in the d'BestO business operations. The results indicate that the implementation of the contract in the d'BestO franchise encompasses two main elements: 1) A partnership based on the syirkah mudharabah contract, where investors only contribute funds while d'BestO fully manages business operations; and 2) Self-management, where partners only purchase and use the rights to d'BestO's brand and business system. The application of the syirkah contract in the d'BestO franchise is found to be in accordance with Islamic economic law principles, particularly in terms of transparency and clarity of transactions. Keywords: syirkah contract, franchise, Islamic economic law, d’BestO